Pengaruh Model Problem Based Learning (PBL) Berbantuan Media Kartu Soal Berbasis Canva Terhadap Kemampuan Berpikir Kritis Siswa SD - Jidan Fauzi; Sofyan Iskandar; Tiara Yogiarni (LPPM Institut Pendidikan Nusantara Global, 2026)
Critical thinking skills play an essential role in elementary education; however, students' critical thinking abilities remain relatively low. This study aimed to: (1) examine the effect of the Problem-Based Learning (PBL) model assisted by Canva-based question card media on elementary students' critical thinking skills, and (2) compare the improvement in critical thinking skills between students taught using the PBL model and those taught using the Discovery Learning model. This study employed a quasi-experimental method with a nonequivalent control group design involving 50 fourth-grade students, consisting of 25 students in the experimental class and 25 students in the control class. Data were collected using pre-test and post-test critical thinking tests and analyzed through normality, homogeneity, independent sample t-test, and simple linear regression. The findings revealed that the PBL model assisted by Canva-based question card media had a significant positive effect on students' critical thinking skills. Furthermore, students in the experimental class demonstrated significantly higher improvement than those in the control class. Therefore, the PBL model assisted by Canva-based question card media can serve as an effective alternative learning strategy to enhance elementary students' critical thinking skills.